From Graduation to Professional Practice: EFL Students’ Self-Reported Collaboration Competence in Indonesian Higher Education - Hidayatullah Yunus; Nadhiyah Putri Wahdana (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
Collaboration competence has become an essential attribute in higher education, particularly in preparing graduates for increasingly complex and team-oriented professional environments. However, the extent to which collaborative learning in university settings aligns with workplace demands remains insufficiently understood, especially in the context within English as a Foreign Language (EFL) in Indonesia. This study aims to examine how collaboration competence is perceived at the point of graduation and how it is subsequently experienced in professional contexts among Indonesian EFL graduates. Adopting a mixed-method design, the study combines quantitative data from a tracer study questionnaire involving 295 alumni (graduates of 2023–2025) and qualitative insights from semi-structured interviews with three participants representing each cohort. Quantitative findings reveal a consistent shift in perception, with collaboration competence rated predominantly as “high” at graduation and “very high” in workplace contexts. Qualitative findings further indicate that collaboration competence develops over time, moving from passive participation toward more active, agentic, and sometimes leadership-oriented engagement. The study also identifies key challenges, including unequal participation and communication difficulties, as well as the importance of structure, accountability, and technology-mediated collaboration. Overall, the findings suggest that collaboration competence is not a fixed outcome of higher education but a context-dependent and evolving practice shaped by workplace experiences. This study contributes to the need for higher education to design more structured and authentic collaborative learning environments that better reflect workplace realities.